СЕМЕЙСТВЕННЫЙ СПЕКТР ФЛОРЫ СЮГАТЫ - БОГУТИНСКОГО МАССИВА. (Eurasian Journal of Ecology, 2016)
In article is resulted analyzes the spectrum of familial flora Syugaty-Bogutinskogo low-mountain massif. A study of familial spectrum recorded 85 families, of which 10 leading family make 61,31 % from the flora of region. The leading place is occupied by the family Asteraceae, which includes 129 species belonging to 52 general.